(untitled) (Journal of actual problems of jurisprudence, 2023)
In a country that occupies a leading position in the world in terms of land area, the land dispute has not yet entered the agenda, including the issue of rational use and protection of natural pasture lands. According to official data, 94.3 million hectares of pasture land have been put into operation in the republic. Only 36 percent of pastures are used for animal husbandry, and the remaining share is among free land. Most of the pasture land that is not utilized belongs to legal entities, that is, according to the president, "Latifundists". As for pasture lands, President Kassym-Jomart Kemelevich Tokayev, at an expanded meeting of the Government on January 26, 2021, instructed the state to return pasture lands that have become the property of individuals and serve for the benefit of the rural population. On February 20, 2017, the Law of the Republic of Kazakhstan «On Pastures» (hereinafter referred to as the Law) was adopted. The law is aimed at the development of effective regulation of pasture lands, including the rational use of pastures and the improvement of their infrastructure, and the prevention of land degradation processes. The norms adopted in accordance with articles 13-15 of the law and article 84 of the Land Code provide for the rational use of pasture lands aimed at meeting the economic needs of those involved in animal husbandry. However, there are a number of shortcomings in the law, for example, since 2015, control over agricultural land has been the responsibility of akimats. Here, local executive bodies should determine undeveloped lands in advance, but in practice, local executive bodies neglect the control of pasture lands too much, normative legal acts adopted in accordance with Article 13 of the Law - plans for pasture management and their use are not officially implemented in the regions, are superficial. The maps and diagrams presented in the plans do not contain the information provided for by the current legislation. Outer rangelands are state-owned, but residents cannot independently graze livestock on these areas. In accordance with the current legislation, the joint use of this land plot is provided, that is, the population unites, becomes a whole village, produces a herd and appreciates livestock. The norms of agrarian and land legislation, which take place in the mechanism of legal regulation of the use and protection of natural pastures, do not fully ensure their rational use and protection in the context of the transition to a «green» economy of the country. The authors in the article strengthened the requirements of the Law of the Republic of Kazakhstan «On pastures», including in terms of drawing up, approval and practical application of pasture management plans, and special attention is paid to the implementation of articles 13, 15 of this law and subparagraph 4-1) of paragraph 2 of article 84 Land Code of the Republic of Kazakhstan. Key words: pastures, animal husbandry, land ownership, agriculture, natural pastures, natural water sources, legal entity, latifundist.